2014
DOI: 10.1111/apa.12685
|View full text |Cite
|
Sign up to set email alerts
|

Children with asthma have significantly lower long‐term cortisol levels in their scalp hair than healthy children

Abstract: Long-term cortisol levels were significantly lower in children with asthma than healthy children. Measuring long-term cortisol levels in scalp hair is an attractive, noninvasive tool that can evaluate the effect of asthma and its treatment on the hypothalamic-pituitary-adrenal axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…The results of a recent study analyzing hair cortisol in children with asthma receiving ICS were similar to our findings with reported cortisol levels twofold lower than those in children without asthma (24). However, it was unknown whether the decrease in cortisol was due to the inflammatory condition itself or due to the effect of ICS.…”
Section: Resultssupporting
confidence: 89%
“…The results of a recent study analyzing hair cortisol in children with asthma receiving ICS were similar to our findings with reported cortisol levels twofold lower than those in children without asthma (24). However, it was unknown whether the decrease in cortisol was due to the inflammatory condition itself or due to the effect of ICS.…”
Section: Resultssupporting
confidence: 89%
“…Two pilot case-control studies similar to the present study have been published [20, 21]. In contrast to our finding, Kamps et al [20] concluded that HCC in asthmatic children treated with ICS (median 2.0 pg/mg; 95% CI 1.4–4.1) was “significantly” lower than HCC in healthy children (4.3 pg/mg; 95% CI 1.8–5.9, p value not reported). Of note, while markedly different means are reported, the distribution of HCC of both the asthmatic and the control group completely overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding HCC in asthmatic children with ICS therapy are scarce [20, 21]. The aim of this case-control study was to compare long-term cortisol concentrations in scalp hair of asthmatic children receiving ICS treatment with those of healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reduced ACTH levels in CF children may be a sign of both hyperand hypocortisolaemia associated with the abnormal driving of the hypothalamic-pituitary-adrenal (HPA) axis by repeated lung disease exacerbations and chronic systemic low-grade inflammation [36] . While impaired adrenal response and HPA axis exhaustion are well documented in asthma and non-CF bronchiectasis [37][38][39] , similar findings in CF patients have been limited. To our knowledge, only the recent study by Laguna et al [40] has demonstrated decreased plasma cortisol concentrations in CF patients (aged 13.6-38.5 years) during acute pulmonary exacerbations.…”
Section: Discussionmentioning
confidence: 99%